Model Konseling sebaya Berbasis Budaya Pesantren Untuk Meningkatkan Penyesuaian Diri - Rokhmatika, Nailu; Roikhatul Janah (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
Self-adjustment is a crucial ability for new students (santri) in adapting to the pesantren environment, which is characterized by its unique culture and strict regulations. Many santri face adaptation challenges that can negatively impact their comfort and academic performance. This study aims to develop a peer counseling model based on pesantren culture as a strategy to enhance the self-adjustment of new santri. Using a Research and Development (R&D) approach, this study follows three main stages: initial information gathering, planning, and model development. The outcome of these stages is the formulation of a peer counseling model contextualized with pesantren values such as solidarity, simplicity, and obedience to religious teachings. This model is expected to serve as a practical guide for counselors and educators in assisting new santri to overcome adaptation difficulties effectively through trained peer support. The findings contribute theoretically to the development of culturally-based guidance and counseling, and offer practical benefits in improving the psychological well-being of students in the pesantren environment